Management of the Da'wah of the National Committee for the Palestinian People in the Palestine Concern Action in Medan City - Siti Wahyummi Nur Jannah; Abdullah Abdullah (International Journal of Emerging Issues in Islamic Studies, 2024)
The Palestinian issue positions the National Committee for the Palestinian People (KNRP) as a humanitarian organization dedicated to aiding and supporting Palestinian independence, necessitating effective execution of da'wah activities. Da'wah's enduring relevance is attributed to its adaptability to contemporary needs, with its management process significantly impacting the attainment of its goals through the structured organization of human and other resources. Commencing with the current matter, this research aims to describe the Da'wah activities of KNRP, which are managed in actions to care for Palestine in Medan City, starting from planning da'wah activities, organizing, actuating, to controlling and evaluating da'wah activities. The subjects of this research are the administrators of the National Committee for the Palestinian People in Medan City, Indonesia. The author used an interview method to collect this information from three sources and documentation: books, journals, photos, videos, and official websites. The research results relate to four management functions. First, KNRP's missionary planning is to carry out outreach and education about the Palestinian problem by gathering moral and material support from various elements of society. Second, the da'wah organization at KNRP is divided into core volunteers and freelance volunteers. Core volunteers are registered in the management structure and consist of regional, program, and operational coordinators. Third, the implementation of da'wah at KNRP involves carrying out work programs that were created at the beginning based on the KNRP vision and mission. Distribute humanitarian aid from the community to the Palestinian people and collaborate with various parties within and outside the country. Fourth, KNRP da'wah is monitored by providing fixed procedures for every existing activity and creating an annual evaluation forum for monthly and national working meetings.